Determinants of foreign direct invesment in eight ASEAN countries - Rastiati, Rastiati; Khoirudin, Rifki (Universitas Ahmad Dahlan, 2024)
This research aims to analyze the influence of economic growth, labor, regulatory quality, political stability, and carbon emissions on Foreign Direct Investment (FDI) in eight member countries of the Association of Southeast Asian Nations (ASEAN). With strong economic growth, a qualified workforce, good regulations, stable politics, and low environmental degradation, ASEAN member countries have great potential for investment, which generates long-term returns. This makes the ASEAN region interesting to analyze the factors that influence FDI in the region. Using the Seemingly Unrelated Regression (SUR) method and secondary data from the World Bank, this study combines cross-sectional and time-series data to provide a comprehensive overview. The research findings indicate that variables such as labor, regulatory quality, political stability, and carbon emissions have a significant impact on foreign direct investment in ASEAN countries. These findings underscore the importance of these factors in determining the direction and volume of foreign investment. This study contributes significantly to understanding the dynamics of foreign investment in the ASEAN region and highlights the importance of efforts to improve political stability, regulatory quality, and manage carbon emissions to drive economic growth through foreign capital inflows. The implications of these findings can serve as a policy foundation for governments and stakeholders in ASEAN to enhance the attractiveness of foreign investment.